Education for Clean and Healthy Lifestyle in Preventing Covid-19 for Elementary School Students 1 Maleber Ciamis - Dewi Afrianti; Grida Saktian Laksito (Research Collaboration Community (RCC), 2021)
The implementation of education regarding healthy clean living behavior is a form of community service, with the aim of being able to help elementary school students to increase their understanding of the importance of maintaining clean and healthy behavior to avoid the spread of the Covid-19 virus. COVID-19 causes a disease that attacks the respiratory system in humans. This virus has infected millions of people, causing a high mortality rate for sufferers throughout the world, both children and adults so that education about clean and healthy living behavior is one form of prevention to avoid the Covid-19 virus. The method of activity in this community service uses a follow-up study method with a participatory approach. The educational materials provided to the students of SD 1 Maleber include an introduction to COVID-19 and its symptoms, how to wash hands properly and correctly, how to apply cough etiquette, how to apply physical distancing, and how to apply a clean and healthy lifestyle. Educational activities are carried out by providing counseling to PHBS by using lecture, discussion, question and answer methods, and demonstrations. Submission of material is also done using learning media in the form of posters. The results of this study are to provide knowledge of participants who are students of Elementary School 1 Maleber Ciamis where previously they felt indifferent and felt they did not maintain clean and healthy behavior. After participating in educational activities for clean and healthy living habits, students will understand the importance of maintaining a healthy and clean lifestyle, gain knowledge in preventing the spread of the COVID-19 virus by applying cough etiquette, washing hands thoroughly, maintaining distance, and always maintaining health.